2014
DOI: 10.1111/iar.12076
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene coral reef environment recorded in Tridacnidae shells from archaeological sites in Okinawa‐jima, subtropical southwestern Japan

Abstract: Seasonally resolved records of carbon and oxygen isotopic composition (δ18O) in fossil shells of giant clams (Tridacnidae) recovered from the Kogachibaru Shell Mound (26°26′N, 127°49′E) and the Second Aragusuku‐Shichabaru Ruin (26°18′N, 127°46′E) in Okinawa‐jima, southwestern Japan, were investigated to reconstruct subtropical coral reef environments of the past. The samples, mainly composed of aragonite shells with limited amounts of diagenetically‐altered calcite cements, were selected for geochemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The δ 13 C shell values show no statistically significant ontogenetic trend. Previous studies have shown the same results in the inner shell layers of other tridacnids [ 32 , 35 , 38 , 55 ]. In contrast, distinct ontogenetic decreases in δ 13 C values have been detected in some bivalves [ 58 – 60 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The δ 13 C shell values show no statistically significant ontogenetic trend. Previous studies have shown the same results in the inner shell layers of other tridacnids [ 32 , 35 , 38 , 55 ]. In contrast, distinct ontogenetic decreases in δ 13 C values have been detected in some bivalves [ 58 – 60 ].…”
Section: Discussionsupporting
confidence: 80%
“…This is true for the inner shell layers of not only T . derasa but also other tridacnids [ 35 , 38 , 53 55 ]. These indicates that such a link is unlikely because only minor amounts of metabolic carbon are incorporated into the bivalve shells as shown in non-zooxanthellate bivalves [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asami et al . () present seasonally resolved records of carbon and oxygen isotopic compositions (δ 18 O) in the fossil shells of giant clams recovered from archeological sites in Okinawa, Japan. Results demonstrate that the annual mean seawater temperature and salinity at Okinawa were approximately 1–3°C higher and 1–2 lower, respectively, at 4000 yr cal.…”
mentioning
confidence: 99%